Statistical Analysis of the Andalusian Incomes During the Year 2021 - Ceballos González, Manuel; de la Puerta Belzunegui, Jose María (Unidad Editorial UPTC, 2023)
Andalusia is one of the autonomous communities of Spain with the highest economic growth. The main goal of this paper is to analyse the budgets in every city and town of Andalusia during the year 2021. In order to do so, we have developed a statistic analysis for the variable income per capita by using Stata software and a database. Stata is a powerful statistical software whose first version is from 1985. It is very common to use this software to deal with problems regarding big data. The database considered corresponds to the Mutiterritotial Information System from the website of the Institute of Statistics and Cartography of the Junta de Andalucía. The results obtained allow us to conclude that in Andalusia there are statistically significant differences with respect to both at the municipal and provincial level. This yields to the existence of atypical and highly atypical data. After various tests, it has been concluded that the data for the incomes per capita does not fit a normal behaviour and that there exists a strong correlation between this variable and other variables from the database. JEL Codes: C10, C14, L10 Received: 04/09/2023.  Accepted: 14/11/2023.  Published:  22/12/2023.